OSTEOPOROSIS IN PATIENTS WITH SPINAL CORD INJURY - Kurtuluş Kaya,; Sibel Ünsal,; Sumru Özel, (Archives of Rheumatology, 2005)
Calcium loss from bone in a short time after injury is one of the result of spinal cord injury (SCI). Sequence of the events that results with bone loss is not known exactly. The main findings in patients with spinal cord injury are; dramatic increase in bone degradation after a short time from the beginning and decrease in osteoblastic activity. Bone mass loss occurs as a consequence of increase in remodelling and bone resorbtion that passes bone formation. Even though this problem is known approximately for 50 years, cause of osteoporosis in spinal cord injured patients is not completely understood. It is considered that the events appears with deafferantation of the sympathic nerve system causedby the neurologic lesion may take an important role at immobilization.